1,4-bis(2,2-diphenylethenyl)benzene as an efficient emitting material for organic light emitting diodes - Fenenko, L.; Guoliang Mao; Akihiro Orita; Junzo Otera; Smertenko, P.; Svechnikov, G.; Jun-ichi Nishide; Hiroyuki Sasabe; Chihaya Adachi (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
We report on the photophysical properties of 1,4-bis(2,2-diphenylethenyl)benzene (PEB) in a solution and a solid state. A poor blue photoluminescence efficiency of PEB in a solution dramatically increases in the deposited film. We explain such properties in terms of molecular dynamics and degrees of intramolecular freedom in various molecular environments. PEB as an electron-transport and emitting layer in organic light-emitting diodes (OLEDs) shows bright blue-green electroluminescence (EL) with the peak wavelength at λmax ~ 495 nm. The maximum external EL quantum efficiency of ηEL = 2.5 % and maximum luminance of 41600 cd/m2 in the optimized device were obtained, indicating that PEB possesses superior electron-transport ability.